Mānasa-mīmāṃsā, athavā, Gosvāmī Tulasīdāsa Jī krta "Rāmacaritamānasa" kī eka nishpaksha samālocanā - Śāstrī, Rajanīkānta (SAMP early 20th-century Indian books project ;, 1949)
Critical study of Rāmacaritamānasa of Tulasīdāsa, 1532-1623.